Nutritional Control of Elongation of DNA Replication by (p)ppGpp - Wang, Jue D. (2007)
DNA replication is highly regulated in most organisms. Although much research has focused on mechanisms that regulate initiation of replication, mechanisms that regulate elongation of replication are less well understood. We characterized a mechanism that regulates replication elongation in the bacterium Bacillus subtilis. Replication elongation was inhibited within minutes after amino acid starvation, regardless of where the replication forks were located on the chromosome. We found that small nucleotides ppGpp and pppGpp, which are induced upon starvation, appeared to inhibit replication directly by inhibiting primase, an essential component of the replication machinery. The replication forks arrested with (p)ppGpp did not recruit the recombination protein RecA, indicating that the forks are not disrupted. (p)ppGpp appear to be part of a surveillance mechanism that links nutrient availability to replication by rapidly inhibiting replication in starved cells, thereby preventing replication fork disruption. This control may be important for cells to maintain genomic integrity.